Haemorrhagic ulcerative duodenitis in a patient with COVID-19 infection: clinical improvement following treatment with budesonide - Frank Tacke; Ibrahim Awwad; Selina Greuel; Christian Fischer (BMJ Open Gastroenterology)
We present a case of a male patient in his mid-30s with COVID-19-induced lung failure requiring extracorporeal membrane oxygenation, who needed an emergency oesophagogastroduodenoscopy due to major upper gastrointestinal bleeding. Endoscopy exposed severe ulcerative duodenitis with diffuse mucosal bleeding. While CT angiography did not show any signs of ischaemia, histopathology revealed duodenitis with substantial inflammatory cell infiltrates consisting of neutrophils and CD3+ T lymphocytes with equal CD4+/CD8+ distribution. Since the composition of cell infiltrates coincides with changes in inflammatory patterns of the respiratory mucosa from patients with COVID-19 and in COVID-19-associated enterocolitis, and systemic dexamethasone treatment became standard of care in ventilated intensive care unit patients with COVID-19 infection, we initiated an individualised therapeutic attempt to treat the duodenitis with topical enteral budesonide. Follow-up oesophagogastroduodenoscopies within 4 weeks of enteral budesonide administration revealed a full clinical and histological healing of the duodenal mucosa with marked reduction of neutrophilic and lymphocytic infiltrates.To our knowledge, the current report is the first description of enteral budesonide treatment of duodenitis in a patient with COVID-19 infection and warrants further investigation, whether budesonide might constitute a novel therapeutic strategy for the management of COVID-19-related intestinal mucosal damage.